ANALISIS SEMIOTIKA SOSIAL IKLAN CETAK PARFUM DALAM MAJALAH COSMOPOLITAN - , AGITA RISMA NURHIKMAWATI, Prof. Dr. Soepomo Poedjosoedarmo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Advertisement is one media of communication between company and its consumer. Advertisement persuades consumer to use the product by showing its advantages. This social semiotics study analyzes the system of sign, both verbally and visually, that is used in perfume print advertisements found in magazine Cosmopolitan to build the concept of advantages. The analysis includes form, meaning, and ideology of verbal and visual advertisement structure. In analyzing the data, the writer uses qualitative approach. There are 12 advertisements which taken from Cosmopolitan on September and October 2011 edition. The process of collecting data uses library research technique. Verbal structure of advertisement is analyzed by using the theory of Syntax, while visual structure of advertisement is analyzed by using the theory of sign. The result of this study shows that the advertisements do not fulfill the complete structures. The structures which always appear in perfume print advertisements are lead, display, announcement, verbal emblem, and call-visit information. Syntactically, announcements are in form of VP, DP, NP, or complete sentence. Verbal emblems mostly are in form of NP. Enhancers are in form of sentence. Tags are in form of NP or VP, while call-visit information is in form of AP or NP. Leads and displays are in form of icon, while visual emblems and barcodes for visual call-visit information are in form of symbol. Perfume print advertisements do not show their physical product to show the advantages. The meaning which is established by verbal and visual structures leads to ambiguous interpretation. The ideologies that are carried by the advertisements include definition of beauty, women exploitation, capitalism, and globalization.